Write the equation of the table below.




y - 5 = -2(x - 6)
y - 5 = -2(x - 6)

y - 5 = 2(x - 6)
y - 5 = 2(x - 6)

y - 6 = 2(x - 5)
y - 6 = 2(x - 5)

y - 6 = -2(x - 5)

Write the equation of the table below y 5 2x 6 y 5 2x 6 y 5 2x 6 y 5 2x 6 y 6 2x 5 y 6 2x 5 y 6 2x 5 class=

Respuesta :

Answer:

equation: y = 2x - 7

Step-by-step explanation:

Let equation be y = mx + c

m = (1-(-1))/(4-3) = 2

sub (4, 1):

1 = 2(4) + c

c = -7

This is a question on coordinate geometry. If you wish to venture further into it/understand this topic better, you may want to follow my Instagram account (learntionary), where I post some of my own notes on certain topics and also some tips that may be useful to you :)